Tendon overuse injuries - Ibarra, C. (2001)
Overuse tendon injuries are the result of chronic, micro-traumatic mechanical insul to the tendon, generally associated to a series of underlying predisposing extrinsic factors such as repetitive mechanical load, and equipment-related problems. Intrinsic factors such as tissue vascularity, muscle weakness or imbalance, malalignment, age-related and other systemic factors have also been suggested to be etiologic conditions (1-4). The terms tendinitis and tendinosis have been widely used to address chronic overuse tendon injuries, however, both terms refer to different entities relative to both the pathologic changes in the tissue and the treatment and prognosis of them. Chronic overuse tendon injuries are commonly seen in athletic individuals, and can account for 30% of all running-related injuries (5). Gruchow and Pelletier, have reported a prevalence of almost 40% among tennis players (6). Common site of overuse tendon injuries in athletic individuals are the shoulder (2,7-11) the elbow (2-4,12,13) the hip (4) the knee (2,4,5,14,15) and the ankle (2,4,5,16). Not uncommonly, the micro-traumatic or overuse injury is the result of a repetitive insult secondary to abnormal mechanics of a joint, such as in the case of internal impingement of the shoulder due to anterior hyperlaxity and posterior capsule tightness. In many cases the presence of angiofibroblastic tendinosis results in difficult prolonged treatment and often end up requiring surgical intervention. Surgical treatment generally consists of removal of abnormal tissue and repair of the tendon and its insertion sites (3,7,12,13,15-17). In other instances, surgical treatment is aimed at correcting predisposing factors such as joint instability (Figure 1).7 A comprehensive rehabilitation program during conservative treatment and after surgery focuses on a rest period and modification of activities, technique or gear characteristics. EMG-assisted computerized motion analysis can be useful to modify errors in technique that predispose to injury or as bio-feedback training before returning to sports (Figure 2). Non-steroidal anti-inflammatory medication and physical therapy modalities can be used for treatment of swelling and pain while preserving mobility of affected or adjacent joints. Limited use of local corticosteroids can be reserved to patients with severe pain that prevents them from undergoing rehabilitation . Abuse in the use of injected corticoids has been associated with the development of crystal formation and calcific tendinosis (Figure 3) (3) Stretching and eccentric strengthening exercises is recommended (Figure 4), followed by endurance training and specific sports-related exercises (4)